2019
DOI: 10.1021/acsami.9b04148
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State, Near-Infrared to Visible Photon Upconversion via Triplet–Triplet Annihilation of a Binary System Fabricated by Solution Casting

Abstract: Herein, triplet–triplet annihilation upconversion (TTA-UC) from near-infrared (NIR, 785 nm) to visible (yellow, centered at 570 nm) regions has been demonstrated in the binary solid of condensed chromophores. Microparticles of the binary solid comprising rubrene as a matrix (emitter) and π-extended Pd-porphyrin as a dopant (sensitizer) in a mole ratio of 1000:1 were obtained by solution casting. Excitation intensity dependence and quantum yield (QY) of the upconverted emission were characterized for individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 56 publications
6
91
0
Order By: Relevance
“…29). 43 Interestingly, the film was formed after simple drying of the THF solution of chromophores. Although, 100% sensitizer to annihilator TET, was reported, UC quantum yield was recorded low due to singlet fission promoted fluorescence quenching of rubrene and back energy transfer to the sensitizer in the solid state.…”
Section: Solid State Nir To Vis Molecular Tta-ucmentioning
confidence: 99%
See 2 more Smart Citations
“…29). 43 Interestingly, the film was formed after simple drying of the THF solution of chromophores. Although, 100% sensitizer to annihilator TET, was reported, UC quantum yield was recorded low due to singlet fission promoted fluorescence quenching of rubrene and back energy transfer to the sensitizer in the solid state.…”
Section: Solid State Nir To Vis Molecular Tta-ucmentioning
confidence: 99%
“…Although, 100% sensitizer to annihilator TET, was reported, UC quantum yield was recorded low due to singlet fission promoted fluorescence quenching of rubrene and back energy transfer to the sensitizer in the solid state. 43 To address the issue of singlet fission (SF), induced fluorescence quenching of rubrene, Kazlauskas's research group synthesized t-butyl substituted rubrene (t-butyl-rubrene) as shown in Fig. 30.…”
Section: Solid State Nir To Vis Molecular Tta-ucmentioning
confidence: 99%
See 1 more Smart Citation
“…These results clearly show that IUC is governed by concentration of the triplet species with the 3 DPA* moiety, not by the prepared concentration of the ground state DPA. Employment of Kamada fitting function shown in eqn 5, [35][36][37] !" = #$ $1 +…”
Section: Resultsmentioning
confidence: 99%
“…I TH / mW cm -2 1 2 mM) containing PtOEP (0.05 mM). Kamada fitting function (eqn 5) [35][36][37] was employed.…”
Section: Resultsmentioning
confidence: 99%